2022
DOI: 10.1159/000527386
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Emergence of Appetite and Hunger Resulting in Weight Gain and Improvement of Eating Disorder Symptomatology during and after Short-Term Off-Label Metreleptin Treatment of a Patient with Anorexia Nervosa

Abstract: Off-label treatment of a 15-year-old female patient with anorexia nervosa with human recombinant leptin (metreleptin) for nine days was associated with self-reported increments of appetite and hunger resulting in rapid weight gain, substantial improvement of eating disorder cognitions and of depression. The results further substantiate the effects of metreleptin on both AN and depression. We contrast these results with the widespread view that leptin is an anorexigenic hormone. Randomized controlled trials are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(32 citation statements)
references
References 39 publications
1
30
0
1
Order By: Relevance
“…There is a growing body of evidence that hypoleptinemia in acute AN influences mood and disorder-related rumination and that experimental, well-monitored metreleptin treatment in patients with AN has the potential to reverse or at least improve these and other somatic and neuropsychiatric symptoms of AN. [22][23][24][25] Furthermore, going beyond associations between hypoleptinemia and rostralmedial amygdala nuclei alterations as documented previously, 29 the current study unveiled an impact of a specific subgroup of rostral-medial amygdala nuclei in mediating the relationship between leptin levels and rumination frequency in acute AN. We acknowledge that the observed mediation effects via volumes of right accessory basal and cortical nuclei are preliminary.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…There is a growing body of evidence that hypoleptinemia in acute AN influences mood and disorder-related rumination and that experimental, well-monitored metreleptin treatment in patients with AN has the potential to reverse or at least improve these and other somatic and neuropsychiatric symptoms of AN. [22][23][24][25] Furthermore, going beyond associations between hypoleptinemia and rostralmedial amygdala nuclei alterations as documented previously, 29 the current study unveiled an impact of a specific subgroup of rostral-medial amygdala nuclei in mediating the relationship between leptin levels and rumination frequency in acute AN. We acknowledge that the observed mediation effects via volumes of right accessory basal and cortical nuclei are preliminary.…”
Section: Discussionsupporting
confidence: 72%
“…16,17,20,22 Moreover, case studies in patients with AN reported improvements in hyperactivity, weight phobia, mood, and, importantly, foodÀ/weight-related rumination following short-term treatment with recombinant human leptin (metreleptin). [23][24][25] However, the effects of metreleptin on brain structures/functions, potentially leading to its beneficial cognitive-affective impacts, have not been examined in AN to date.…”
Section: Limitationsmentioning
confidence: 99%
“…The first interview was transcribed according to the transcription rules of Dresing and Pehl [ 25 ]. The interview pursued two aims: (i) focus on the subjective experience of the patient upon the initiation of metreleptin treatment and (ii) investigation of the extent of overlap of induced changes with those previously observed in AN patients [ 15 , 16 , 17 ]. Accordingly, the patient was asked to report all observations she had made within the initial 14 days of metreleptin treatment in a non-directive manner; in the second part of the interview, she was systematically questioned as to potential changes in preoccupation with food, sleep, mood, concentration, and spontaneity.…”
Section: Case Historymentioning
confidence: 99%
“…Due to leptin's role in the adaptation to starvation [ 12 ], we postulated that psychological symptoms of starvation, as meticulously delineated in the Minnesota Starvation Study [ 13 ], may result from the hypoleptinemia induced by loss of fat mass [ 14 ]. Indeed, metreleptin treatment of patients with anorexia nervosa (AN) has recently been shown to entail beneficial and rapid-onset cognitive, emotional, and behavioral effects [ 15 , 16 , 17 ]. Thus, preoccupation with food declined within 3–5 days; sleep improved.…”
Section: Introductionmentioning
confidence: 99%
“…43 In five patients with acute anorexia nervosa and hypoleptinemia, metreleptin treatment was also associated with a pronounced improvement of depressed mood. 31,32,44 Interestingly however, anorexia nervosa associated hyperactivity decreased under metreleptin substitution. 31,32 This finding is in apparent contrast to the increased ratings of motor activity in our patients with CLD.…”
Section: Mean Total Scorementioning
confidence: 96%